Universalidad y sociabilidad. Comentario a un texto kantiano - Artola Barrenechea, José María (Logos. Anales del Seminario de Metafísica, 2002)
This work aims to be an investigation about the kantian idea of History and its relation to the Universal Political Perspective. At the same time the author revails an special review to the kantian’s concepts of Nature and Society in the way of life course and the humanity’s harmony. Finaly this human association, that is Society, appears as Philosophy of History under a hidden plan of Nature that reveals trough its own development.
Keywords: Comunication and Living Together; Constitutions; Philosophy of the History; Civil Mission; Nature’s Project; Universal Politic Perspective; Quiliasmo; Teleology; Rational Theology